Strategi guru pendidikan agama Islam dalam membangun kesalehan sosial siswa SMA Negeri 3 Yogyakarta - Anwar, Khoerul; Sarjono, Sarjono (Indonesian Journal of Educational Management and Leadership, 2023)
Islamic Religious Education in schools should ideally be able to build students' personal piety as well as social piety. Personal piety and social piety are the basic capital for students to be successful in this world and the hereafter. However, the dichotomy of personal piety and social piety still exists today. The purpose of this study was to determine the strategies of Islamic Religious Education teachers in building students' social piety, the supports and constraints they face. This research was conducted at SMA Negeri 3 Yogyakarta. This research method is a descriptive qualitative research method. Data in this study were collected using interviews, observation and documentation. After the data is collected, data analysis is carried out, with the steps: data reduction, data display, decision making, and data verification. Test the validity of the data using triangulation techniques. The results of the study show that: (1) The strategy of PAI teachers in building the social piety of students at SMA Negeri 3 Yogyakarta includes: a) building collaboration with the community, b) improving the quality of PAI learning in class, c) cultivating responsibility through assignments, d) building students' self-awareness for social order, e) Getting used to tolerance towards others, f) building the commitment of the school community, g) involving the role of alumni, h) optimizing the function of the school mosque i) getting students used to praying Dhuhur in congregation, j) fostering an Islamic spiritual section. (2) PAI teacher support in building students' social piety comes from school principals, teachers, students, parents, alumni, the community, and a school environment that is conducive to learning (3) the obstacles faced are in the form of internal factors including: Negative influence of social networking (social media), instant culture among students, gadget addiction.